تحليل كتاب Mahir Berbicara Bahasa Arab لسيف الدين ريطانجا وزملائه على رأي عبد الحميد عبد الله وناصر عبد الله الغالى - Ramadani Dalimunthe; Fadlan Masykura Setiadi; Ria Rafita Supriani (PT. Willy Print Art, 2025)
The purpose of this study is to analyze the cultural, social, psychological, linguistic and educational foundations of the Mahir Bicara Bahasa Arab textbook by Saifuddin Ritanga and his colleagues, according to the opinions of Abdul Hamid Abdullah and Nasser Abdullah Al-Ghaly. Given the type of this research, namely analytical descriptive research. Therefore, the method used by the researcher in analyzing the data is the researcher formulates research questions, the researcher determines the means or sources of data to answer the research questions, formulates the categories used in analyzing the data, and the data collection that can be selected, then presents the content analysis and the results. Based on the presentation and analysis of the data, the researcher came to the following conclusions: The book Mahir Bicara Bahasa Arab by Saifuddin Ritanga and his colleagues is in accordance with the cultural and social foundations. In this book, the researcher found nine cultural and social knowledge, including Islamic culture, Indonesian culture, Mendeling Natal culture, and school culture. As for the psychological basis, it was agreed by Abdul Hamid Abdullah and Nasser Abdullah Al-Ghaly, with the argument that this book should be relevant to daily life and activities, that the contents of this book should be able to motivate students, that this book should be able to help achieve the ideals that have been embedded in the souls of students, that this book should be in accordance with the needs of students, and that this book should be in accordance with the intelligence of students. However, there are still shortcomings in the linguistic basics.